A Study on the Effect of Monetary Policy on Indian Stock Market with Reference to Bombay Stock Exchange: The Impact of Monetary Policy on the Indian Stock Market (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The Monetary policy make use of various instruments like CRR, SLR, Repo, Reverse Repo, Bank rate and MSF to control the money supply of the country. The SP index BSE 30 is influenced by the monetary policy of RBI. The monetary policy may have a favourable or adverse impact on the stock market. Any change in the monetary policy has a direct impact on stock return and overall economy of the nation. The stock price tends to fluctuate before and after the monetary policy is announced. The study aims to determine the impact of monetary policy over Indian stock market. This study has used secondary data which are collected from various authenticated sources. The Collected data were analysed through average and Correlation methods.The study revealed that there is a perfect negative relationship between monetary policy and BSE 30. This means the relationship is inverse as one variable increase the other variable decrease.